Tembang Macapat: Eksklusifitas Bentuk, Aspek Nilai, dan Pendekatan Pembelajarannya - Udjang Pairin M. Basir (Discovery, 2024)
"Tembang macapat" is part of traditional Javanese art that has special characteristics. From the aspect of its verbal form, tembang macapat is included in the category of bound (non-free) poetry. It contains guru lagu, guru wilangan, and guru gatra, each of which binds in each creation of the lines of the tembang verses and also the technique of singing it. As part of the expression of the soul, this type of tembang contains exotic and exclusive values. In addition to its distinctive form, in "tembang macapat" there are certain messages related to the philosophical and didactic values ​​in each type of tembang. However, from the pragmatic aspect and its application in today's society, the prospects are less encouraging. This is due to the weak factors of development and preservation in society, especially cultural connections in the younger generation. The phenomenon of the shift in the direction of global culture must certainly be a consideration in the direction of the development of tembang macapat, both in format and content so that in terms of connectivity it is part of a portrait of the mindset of its era that is more practical, accommodating, expressive, and functional.